The Effect of Physical Fitness on The Grade Point Average of Students of Physical Education at STKIP Taman Siswa Bima - Rabwan Satriawan (Kementerian Pendidikan Tinggi (KPT), Malaysia, 2019)
Link to publisher's homepage at http://www.mohejournal.com/index.php/mohe